2023
DOI: 10.1002/anie.202300759
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the Buried Interface for Robust Formamidinium‐based Sn−Pb Perovskite Solar Cells with NiOxHole‐Transport Layers

Abstract: Low band gap tin‐lead perovskite solar cells (Sn−Pb PSCs) are expected to achieve higher efficiencies than Pb‐PSCs and regarded as key components of tandem PSCs. However, the realization of high efficiency is challenged by the instability of Sn2+ and the imperfections at the charge transfer interfaces. Here, we demonstrate an efficient ideal band gap formamidinium (FA)‐based Sn−Pb (FAPb0.5Sn0.5I3) PSC, by manipulating the buried NiOx/perovskite interface with 4‐hydroxyphenethyl ammonium halide (OH‐PEAX, X=Cl−,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…The change in electron cloud density may be attributed to the fact that the nitrogen in –NH 2 and oxygen in –OH with lone pairs of electrons can coordinate with the uncoordinated Sn 4+ in SnO 2 , which induces electron transfer from nitrogen and oxygen elements in HAL to SnO 2 . 34,35 The result of Sn 3d spectra confirms the existence of interaction between HAL and SnO 2 . From the O 1s spectra in Fig.…”
Section: Resultsmentioning
confidence: 67%
“…The change in electron cloud density may be attributed to the fact that the nitrogen in –NH 2 and oxygen in –OH with lone pairs of electrons can coordinate with the uncoordinated Sn 4+ in SnO 2 , which induces electron transfer from nitrogen and oxygen elements in HAL to SnO 2 . 34,35 The result of Sn 3d spectra confirms the existence of interaction between HAL and SnO 2 . From the O 1s spectra in Fig.…”
Section: Resultsmentioning
confidence: 67%
“…Additionally, the ABABr interface modification leads to significant improvements in perovskite film morphology, crystallization, and band alignment. More recently, NiO x NCs were also introduced into the low band gap tin-lead perovskite solar cells (Sn-Pb PSCs) system by Zhou et al [67] By manipulating the buried NiO x /perovskite interface with OH-PEAX (4-hydroxyphenethyl ammonium halide, X = Cl À , Br À , or I À ) interlayer, the film quality of Sn-Pb based perovskite has been improved, resulting in the reducing of the surface defects and the improving of the energy matching. Benefitting from these, a PCE of 20.53 % is acquired for Sn-Pb PSCs, which is the highest PCE of Sn-Pb PSCs based on NiO x NCs.…”
Section: Surface Modification Of Nio X Nc Filmsmentioning
confidence: 99%
“…Introducing the tailored molecules to the interface between the perovskite layer and HTL is a simple strategy to reduce the defects of the perovskite surface, inhibit the redox reaction at the interface, modify the optoelectronic properties of NiO x film, and adjust the morphology of perovskite. [17,51,[54][55] Yang et al [29] reported efficient PSCs based on the modified NiO x by diethanolamine (DEA) with hydroxy and amine functional groups. The DEA could strongly interact with both NiO x and perovskite by Ni‧‧‧N, and Pb‧‧‧O interactions, resulting in improved perovskite film quality.…”
Section: Nickel Oxide (Nio X )mentioning
confidence: 99%